Two contrasting Australian Curriculum responses to globalisation: what students should learn or become - Lingard, Bob; McGregor, Glenda (Curriculum journal (London, England), 2014)
This paper compares two contrasting educational policy responses to globalisation in Australia: the 'New Basics' experiment that occurred in the State of Queensland (2000-2003) and the Australian Curriculum, which is currently being implemented across the nation from preschool to Year 10 in English, history, mathematics and science. These initiatives illustrate the tensions that have continued to mount during the last decade over answers to the question of 'what counts' as the most valuable knowledge and/or skills needed to negotiate the complexities of a rapidly globalising world. Illustrating one international trend of favouring the development of competencies and dispositions, the New Basics project abandoned traditional school subjects for futures oriented, 'real-world' learning. The Australian Curriculum demonstrates a strong return to 'the disciplines', partly as a local backlash against experiments like the New Basics and Outcomes Based Education, but also motivated by the desire to improve the nation's performance on international tests; however, via its framework of 'cross-curriculum priorities' and 'general capabilities', the Australian Curriculum also pays heed to the rhetoric of shaping the individual as the kind of person with the skills and dispositions required by the global millennium citizen and worker.